2020
DOI: 10.1371/journal.pone.0240174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mass dihydroartemisinin–piperaquine administration in southern Mozambique on the carriage of molecular markers of antimalarial resistance

Abstract: Background Mass drug administration (MDA) can rapidly reduce the burden of Plasmodium falciparum (Pf). However, concerns remain about its contribution to select for antimalarial drug resistance. Methods We used Sanger sequencing and real-time PCR to determine the proportion of molecular markers associated with antimalarial resistance (k13, pfpm2, pfmdr1 and pfcrt) in Pf isolates collected before (n = 99) and after (n = 112) the implementation of two monthly MDA rounds with dihydroartemisinin-piperaquine (DHAp)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…However, long-term use of anti-malarial drugs particularly PPQ induced ADR [14]. Previous studies indicated that several mutations of pfcrt (93S, 97Y, 101F, 145I, 343L, 353 V, and 356 T) were related to reducing parasite sensitivity to PPQ [13,14,[36][37][38][39]. In this study, no mutations were detected at loci 93, 97, 101, 145, 343, 350, and 353.…”
Section: Discussionmentioning
confidence: 41%
“…However, long-term use of anti-malarial drugs particularly PPQ induced ADR [14]. Previous studies indicated that several mutations of pfcrt (93S, 97Y, 101F, 145I, 343L, 353 V, and 356 T) were related to reducing parasite sensitivity to PPQ [13,14,[36][37][38][39]. In this study, no mutations were detected at loci 93, 97, 101, 145, 343, 350, and 353.…”
Section: Discussionmentioning
confidence: 41%
“…There is longstanding concern regarding the potential for MDA to introduce widespread drug resistance, such as observed with the use of table salt containing CQ starting in the 1950s ( von Seidlein and Greenwood, 2003 ). However, so far there remains an absence of evidence linking direct MDA using therapeutic doses of an artemisinin-based drug combination (ACT) such as DHAPQ, with emerging drug resistance ( Deng et al, 2018 ; Gupta et al, 2020 ; Landier et al, 2018 ).…”
Section: Impact and Consequences Of Population-level Drug-based Interventions: Smc Mdamentioning
confidence: 99%
“…High prevalence of multiple copies of the plasmepsin 2 ( Pfpm2 ) gene, a marker of piperaquine resistance [ 15 ], has been observed to be associated with DP treatment failure in Southeast Asian countries, where artemisinin resistance is frequent [ 16 18 ]. Studies on African isolates showed varying frequencies of multiple copies of Pfpm2 gene: < 5% in Mozambique [ 19 ], 30.5% and 33.9% in Burkina Faso and Uganda, respectively [ 20 ], and up to 50% in Burundi [ 3 ]. However, in high transmission areas like Africa, the detection of minor clones with amplified Pfpm2 in polyclonal infections (MOI > 1) are challenging.…”
Section: Introductionmentioning
confidence: 99%